GENOTYPIC DIFFERENCES AND GENOTYPE × NITROGEN INTERACTIONS FOR YIELD TRAITS IN BREAD WHEAT - F. U. Khan; F. Mohammad; Raziuddin; Z. Shah; M. Ahmad; Z. Shah (Journal of Animal and Plant Sciences, 2017)
Efficient utilization of nitrogen by major crops has always been an aim in plant breeding research. Several economic and environmental issues urge plant breeders to develop plant varieties that could absorb and use nitrogen more efficiently. Thirty wheat varieties were grown under with (N+) and without nitrogen (N0) condition as an independent experiments at The University of Agriculture, Peshawar during 2013/14 crop season. Significant G × E interactions effects for all traits justified independent analysis of variance, which also displayed significant differences among genotypes for all the studied traits under each nitrogen level. Wheat variety Pirsabak-05 exhibited maximum values for tillers m-2 (131) and 1000-grain weight (51.7 g), Aas-11 for grains spike-1 (81 grains), Shahkar-13 for biological yield (8300 kg ha-1), Tatara-96 for grain yield (3570 kg ha-1) and NARC-11 for harvest index (46.9%). The results of substantial variation for various yield traits across two nitrogen levels indicated that significant genetic variation exists in tested bread wheat cultivars. Thus, this germplasm can be safely used in future breeding program focused on the development of wheat cultivars well suited to low input wheat production system.
Keywords: genotype-environment inetraction; germplasm; denitrification